Restorative Justice: A Comprehensive Shift Towards Victim-Perpetrator Reconciliation and Community Healing: Keadilan Restoratif: Pergeseran Komprehensif Menuju Rekonsiliasi Korban-Pelaku dan Penyembuhan Komunitas - Utami, Rahayu Sri (Indonesian Journal of Law and Economics Review, 2023)
Restorative Justice, as a transformative legal concept, aims to restore relationships and repair the damage caused by criminal acts through reconciliation between victims, perpetrators, and communities. This study employs two primary normative juridical research approaches: the Statute Approach, focusing on the analysis of laws and regulations, and the Conceptual Approach, emphasizing the understanding of legal concepts and doctrines. The integration of these approaches reveals that conventional criminal proceedings often neglect active participation in mediation and problem-solving outside the court, unlike Restorative Justice. The study underscores the importance of restoration, which extends beyond mere compensation to a broader rapprochement, facilitating mutual agreements between the victim and the perpetrator. This paradigm shift towards Restorative Justice has profound implications for legal practice, emphasizing the need for inclusive, humane, and empathetic legal processes that align with social realities and human rights. Highlights: Restorative Justice’s Emphasis: Prioritizes restoration over retribution, facilitating mutual agreements between victims and perpetrators, extending beyond mere compensation. Combination of Research Approaches: Utilizes the Statute and Conceptual Approaches for a comprehensive understanding of legal frameworks and underlying principles. Implications for Legal Practice: Advocates a paradigm shift towards more inclusive, empathetic legal processes, resonating with social realities and human rights. Keywords: Restorative Justice, Statute Approach, Conceptual Approach, Victim-Perpetrator Reconciliation, Community Healing